Copolymer dielectrics with balanced chain-packing density and surface polarity for high-performance flexible organic electronics - Deyang Ji (Nature Portfolio, 2018)
Developing large-scale flexible display technologies calls for new gate dielectric materials balancing the insulating property and molecular packing of organic semiconductors. Ji et al. synthesize a dielectric copolymer contributing with charge mobility of 5 cm2 V−1 s−1 and low operating voltage of 3 V.